Synthesis and Antimicrobial Activity of 1, 2, 4-Triazoles. Issue 1 (2005) - Roy, R. U.; Desai, A. R. R.; Desai, K. R.
Abstract : Several 3-(4'-nitrophenyl)-4-(4"-chloro benzamido)-5-substituted phenyl)-4H-1, 2, 4-triazole (3a-3e) and 3-(4'-nitrophenyl)-4-(4"-methyl benzenesulphonamido)-5-substituted phenyl)-4H-1, 2, 4-triazole (4a-4e) have been synthesised. Representative compounds were screened for antibacterial, antifungal activity. Most of them showed significant antibacterial activity.